PetCare Management System - Kamaruzaman, Puteri Balqis; Mat Rejab, Mazidah (Applied Information Technology And Computer Science, 2025)
The PetCare Management System addresses inefficiencies in pet adoption processes faced by animal shelters. Traditional methods, such as relying on WhatsApp for inquiries and Instagram for promotion, are time-consuming, leading to delays, lost information, and reduced adoption success rates. This project develop a system that automates key operations, integrating features like user registration, adoption tracking, rescue reporting, and location-based event services. Developed using the Waterfall methodology, requirements gathering, system design, implementation, testing, deployment, and maintenance ensure a structured and efficient development process. Designed for shelters like Cares JB, it centralizes adoption, rescue, and event management to improve efficiency. The system includes a mobile web-based application, ensuring functionality and usability through alpha and beta testing. By streamlining operations, it reduces administrative burdens, improves response times, and provides a seamless experience. The system increases adoption success, enhances rescue efforts, and benefits both shelters and animals.